E-lerning na polskich uczelniach – zalety i zagrożenia - Ostenda, Aleksander (Видавництво «Редакція «УП», 2016)
The purpose of this article is to present the development prospects of e-learning at universities in Poland. On the basis of sociological research are familiar with the basic advantages and risks that may be a consequence of distance education.
Keywords: E-learning; szkolnictwo wyższe; kształcenia na odległość